تأثير تشغيل المراجل البخارية عند الحمولات الجزئية على المردود و التآكل - سلامة, أحمد; حسن, هيثم (Latakia University Journal -Engineering Sciences Series, 2019)
يهدف هذا البحث إلى دراسة تقليل تآكل مسخنات الهواء في المراجل البخارية التي تعمل عند الحمولات الجزئية, وزيادة مردودها, من أجل ذلك تمت دراسة عمل مرجلين: يحوي الأول ثلاثة مسخنات لهواء الاحتراق, بينما يحوي الثاني مسخنين. أظهرت النتائج تآكلاً فعالاً في مسخنات هواء المرجل الأول بينما كان مردوده أعلى من مردود المرجل الآخر, الذي كان تآكل مسخنات الهواء فيه أقل.كما أظهر هذا البحث أن المحافظة على درجة حرارة لغازات العادم أعلى من نقطة الندى لحمض الكبريت عن طريق إنقاص سطح التبادل الحراري لمسخن الهواء الأول حتى1900m2 تؤدي إلى تخفيض التآكل في المسخن الأول, و زيادة مردود المرجل بحوالي2% وتخفيض استهلاك الوقود بنسبة 2% . This research aims to study the reduction of air heaters' corrosion in steam boilers that work at partial loads, and to increase their efficiency. Therefore, the work of two boilers were studied: the first one contains three air heaters, while the other one contains two. The results showed an active corrosion in air heaters of the first boiler; however, its efficiency was higher than that of the other boiler, in which the air heaters showed lower corrosion. This research also showed that maintaining the exhaust gases temperature above the dew point of sulfuric acid by decreasing the heat exchange surface of the first air heater up to 1900m2 will lead to corrosion reduction in the first heater, increasing the boiler efficiency almost 2% and reducing the fuel consumption 2% .